Everyday multiculturalism: Theorising the difference between 'intersectionality' and 'multiple identities' - Werbner, Pnina (Ethnicities, 2013)
This paper contrasts intersectionality, the negative definition of identities, and multiple identities, the situational valorisation of positive identities, to argue for a generational shift in the performance of everyday multiculturalism in Britain. In everyday encounters, actors work to sustain the definition of the situation (Goffman) and with it a surface of civility and mutual respect which are nevertheless morally compelling. Everyday relationships flow smoothly and naturally, in an unreflexive, taken-for-granted way, to constitute shared positive identities (Schutz). Such surface civility may, however, be disrupted by communicative breakdowns whenever participants do not share implicit systems of relevancy. Deconstructive analyses that probe beneath the surface of the everyday can also reveal the existence of negative identities, subject to discrimination and stigmatisation. This paper contrasts the experience of first-generation Commonwealth immigrants to Britain with that of successive generations, who unreflexively displayed a shared British identity during the London 2012 Olympics.